The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00402-015-2222-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome assessment after total joint replacement: comparison of questionnaire completion times on paper and tablet computer

Abstract: Electronic PRO data collection can substantially decrease time, logistics, and effort associated with questionnaire completion in daily clinical practice. It is also acceptable for use in an older arthroplasty population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…With a mean completion time of 5.2 min we think it is reachable to encourage patients to complete our questionnaires. Moreover, in literature the completion times of paper questionnaires are reported to be significant longer compared to online questionnaires when data entry time is studied[7]. …”
Section: Discussionmentioning
confidence: 99%
“…With a mean completion time of 5.2 min we think it is reachable to encourage patients to complete our questionnaires. Moreover, in literature the completion times of paper questionnaires are reported to be significant longer compared to online questionnaires when data entry time is studied[7]. …”
Section: Discussionmentioning
confidence: 99%
“…PRO is a modern scientific approach widely used in evaluating outcomes of clinical trials based on patient-centered evidence [31-33]. PRO is defined as any report of the status of a patient’s health condition that comes directly from the patient, without interpretation of the patient’s response by a clinician or anyone else [34].…”
Section: Methodsmentioning
confidence: 99%
“…Although not used in this study, prior studies validate individualized recruitment strategies to increase patient engagement. 10,13,26 Possible explanations for our observed response rate may stem from the accessibility and convenience of tablet-based surveys. One group found that e-mail-based follow-up of patients who declined initial survey resulted in a significant response rate, with responders of this approach reporting that a direct approach and immediate survey access contributed to their amenity to engagement.…”
Section: Figurementioning
confidence: 97%
“…15,25 However, delivery models described in the literature contain substantial methodological differences, including various clinical settings, patient characteristics collected, and survey technologies. 15,17,[26][27][28][29] Many cases fail to report participation rate. 17,30 A prior study demonstrates the collection of patient-reported outcomes (i.e., PROMIS physical functional scale) at an academic cerebrovascular clinic using an electronic platform over a time frame of 33 months, reaching 1,946 stroke patients.…”
Section: Figurementioning
confidence: 99%